2014
DOI: 10.1016/j.clinbiomech.2013.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical biomechanics of instability related to total knee arthroplasty

Abstract: Background: Tibiofemoral instability is a common reason for total knee arthroplasty failure, and may be attributed to soft tissue deficiency and incorrect ligament balancing. There are many different designs of implant with varying levels of constraint to overcome this instability; however there is little advice for surgeons to assess which is suitable for a specific patient, and soft tissue balance testing during arthroplasty is very subjective. Method: The current theories on primary and secondary soft tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 88 publications
3
52
0
2
Order By: Relevance
“…Knowledge of the complex kinematics of the native knee is a prerequisite for a successful reconstructive procedure, because preservation of the native knee kinematics is likely to result in superior clinical outcomes [1][2][3][4][5]. The behavior of the knee in the coronal plane has recently become of particular interest, as several authors have shown that failure to restore proper coronal plane knee kinematics during reconstructive knee surgery may result in specific patterns of medial-lateral knee instability, especially in the range of mid-flexion (30 to 45°) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the complex kinematics of the native knee is a prerequisite for a successful reconstructive procedure, because preservation of the native knee kinematics is likely to result in superior clinical outcomes [1][2][3][4][5]. The behavior of the knee in the coronal plane has recently become of particular interest, as several authors have shown that failure to restore proper coronal plane knee kinematics during reconstructive knee surgery may result in specific patterns of medial-lateral knee instability, especially in the range of mid-flexion (30 to 45°) [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For knee arthroplasty patients, the MCL may play an even more crucial role, as other stabilizing ligaments are often sacrificed during surgery (e.g. the anterior cruciate ligament) [5], and maintaining a stable knee can be critical to implant success [610] and patient satisfaction [11]. The MCL is also frequently injured as it is involved in 42% of all ligamentous injuries in the knee [12].…”
Section: Introductionmentioning
confidence: 99%
“…The PCL is in cruciate retaining knee arthroplasty systems one main factor to control anterior-posterior translation [2-4] and is also responsible for the amount of joint compression [5]. However, to quantify the amount of ligament release and its effect on load bearing and kinematics in TKA is complex and limited both in vivo and in vitro .…”
Section: Introductionmentioning
confidence: 99%